2014
DOI: 10.14233/ajchem.2014.17974
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Studies on Chitosan Functionalized Multiwalled Carbon Nanotube Reinforced Epoxy Bionanocomposites

Abstract: The chitosan functionalized multiwalled carbon nanotubes reinforced epoxy bionanocomposite (CS-g-MWCNTs/EP) was developed. Chitosan (CS) was grafted to multiwalled carbon nanotubes (MWCNTs), first by reacting the oxidized carbon nanotubes (MWCNT-COOH) with thionyl chloride to form acyl-chlorinated multiwalled carbon nanotubes (MWCNT-COCl) followed by subsequent dispersion in chitosan. The chitosan grafted multiwalled carbon nanotubes (CS-g-MWCNTs) were reinforced in the epoxy matrix using high speed stirrer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Epoxy resin belongs to a group of thermosetting polymers that are commonly used in engineering applications due to their high performance (excellent mechanical properties, high thermal and corrosion resistance, etc.) and versatility [ 2 , 3 , 4 , 5 ]. It is reported that approximately 323,000 tons of epoxy resin are produced annually, of which 45,000 tons are used in the transportation industry (14%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin belongs to a group of thermosetting polymers that are commonly used in engineering applications due to their high performance (excellent mechanical properties, high thermal and corrosion resistance, etc.) and versatility [ 2 , 3 , 4 , 5 ]. It is reported that approximately 323,000 tons of epoxy resin are produced annually, of which 45,000 tons are used in the transportation industry (14%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a rich scientific literature regarding the investigation of chitosan-and epoxybased coatings; however, these are hybrid systems or composites. For instance, it was observed that the addition of chitosan decreased the tensile strength [19], increased the flexibility [20], improved the hardness of an epoxy composite [21], enhanced the anticorrosion property of epoxy coatings [22], and increased the water absorption of the epoxy-based composite [23]. However, to the best of our knowledge, there are no published data for using them as superposed monolayers formed with dip-coating and specialized for temporary protection during the transport of metals that require further processing or assembly.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that petroleum-based polyamines have been widely used as curing agents for epoxy resin and classified as toxic materials. The polyamines adduct types sometimes were employed to reduce the toxicity [11]. It was previously reported that chitosan nanofibers were used to improve the thermal and mechanical properties of the epoxy resin cured with polyamines [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The polyamines adduct types sometimes were employed to reduce the toxicity [11]. It was previously reported that chitosan nanofibers were used to improve the thermal and mechanical properties of the epoxy resin cured with polyamines [10][11][12][13]. The development of eco-friendly epoxy and hardener based on 2 of 16 biopolymers is very important to produce green coatings.…”
Section: Introductionmentioning
confidence: 99%